Theater in the classroom, classroom in the theater theater arts in the alternative ESL learning system - Abbot, Lenaur B. (2006)
This research proposed an alternative ESL learning system with the creative integration of Theater Arts. The research attempts to provide patterns of instructional innovations to develop the English fluency of elementary pupils raised in a multilingual community. Therefore, it documented the salient instructional processes of the language learning sessions, the rehearsal and staging process of the theater production. In making theater arts as the essential component of the alternative learning system, the creative mechanism and creative spaces of the expressive art form, are defined in this study. They are utilized as the instructional tools to provide the multilingual learners with rich language comprehensible inputs, context-embedded activities that enrich the cognitive process of English instruction. This study used an experimental method of research design, making half of the class population of grade three and grade four pupils as respondents of the experiments and the participants of the program; and the rest, the nonparticipants, were the control group. The researcher conducted a pretest and posttest to both groups before and after the implementation. The test components covered audio discrimination, structural analysis, listening and reading comprehensions, vocabulary and spelling test, and oral proficiency test. The experiment results showed there were observed increases in mean test scores for each of the test components in both groups. However, for all of these components, the observed scores appeared higher in the experimental group. The integration of theater arts in the system fulfills the objectives to establish a highly contextualized, democratic, dynamic, creative and learner-centered English classroom.
Chapter I. Introduction -- Chapter II. Review of related literature -- Chapter III. Framework -- Chapter IV. Methodology -- Chapter V. Scenes of transitions : preimplementation phase -- Chapter VI. Theater in the classroom, classroom in the theater -- Chapter VII. Four walls and beyond : program evaluation -- Chapter VIII. Curtain call : the merging of theater arts and English instruction -- Conclusion -- Recommendation -- Bibliography -- Appendix A. Instructional strategy plan -- Appendix B. Statistical figures of the experiment -- Appendix C. Sample test questions and evaluation tools -- Appendix D. Pictures -- Appendix E. Sample worksheets and outputs -- Appendix F. Theater production matters.
"September 2006".
Thesis (M.A. Theater Arts)--University of the Philippines Diliman.
Keywords: Education in the theater -- Philippines; Drama in education -- Philippines; Children's theater -- Philippines; English language -- Study and teaching (Elementary).